2015
DOI: 10.1016/j.jarmac.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Why does the Cognitive Reflection Test (sometimes) predict utilitarian moral judgment (and other things)?

Abstract: The Cognitive Reflection Test (CRT) is thought to correlate with measures of utilitarian moral judgment because it measures system-2 correction of an initial intuitive response. And some theories of moral judgment hold that the same thing often happens when people arrive a utilitarian judgments. We find, however, that CRT-type items (using logic as well as arithmetic) can work just as well when they do not have obvious intuitive answers at predicting utilitarian moral judgment, assessed with self-report questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
336
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(388 citation statements)
references
References 58 publications
(66 reference statements)
18
336
1
Order By: Relevance
“…Inductive pattern recognition was assessed by a short form of the Ravens Advanced Progressive Matrices (Ravens APM; Bors & Stokes, 1998), which circumvents cultural or linguistic knowledge by testing spatial problem-solving skills. Cognitive control was measured by the three-item Cognitive Reflection Test (CRT; Frederick, 2005) and the four-item extension of the CRT (Baron, Scott, Fincher, & Metz, 2014), with questions such as, "All flowers have petals. Roses have petals.…”
Section: Methodsmentioning
confidence: 99%
“…Inductive pattern recognition was assessed by a short form of the Ravens Advanced Progressive Matrices (Ravens APM; Bors & Stokes, 1998), which circumvents cultural or linguistic knowledge by testing spatial problem-solving skills. Cognitive control was measured by the three-item Cognitive Reflection Test (CRT; Frederick, 2005) and the four-item extension of the CRT (Baron, Scott, Fincher, & Metz, 2014), with questions such as, "All flowers have petals. Roses have petals.…”
Section: Methodsmentioning
confidence: 99%
“…The CRT is widely used, but may not measure the most relevant sort of reflection very well (Baron, Scott, Fincher, & Metz, 2015). Similar and convergent measures of analytic thinking and cognitive reflection also similarly predict religious disbelief (Pennycook, Cheyne, Barr, Koehler & Fugelsang, 2014a;Saribay & Yilmaz, 2017), bolstering the claims to generalizability across measures and also, possibly, providing more direct measures of the relevant traits.…”
Section: Future Questions and Constraints On Generalitymentioning
confidence: 99%
“…Cognitive reflection differentially predicts different facets of religiosity (Bahçekapili & Yilmaz, 2017), as well as religious affiliation (Pennycook et al, 2012) and other related constructs (Pennycook, Cheyne, Barr, Koehler & Fugelsang, 2014b;Saribay & Yilmaz, 2017;Yilmaz & Saribay, 2016). And other measures of reflection, as well as CRT items, predict specific religious beliefs such as endorsement of "divine command theory " Piazza & Landy, 2013;Baron et al, 2015), a view that explicitly discourages reflection on the ground that the word of God is beyond human understanding. The present paper can serve as a jumping board for additional cross-cultural exploration.…”
Section: Future Questions and Constraints On Generalitymentioning
confidence: 99%
“…The correct answer is 5 cents. Although the CRT is correlated with cognitive ability and numeracy, research suggests that it explains incremental variance in outcomes, including performance on various judgment and decision tasks (Baron, Scott, Fincher, & Metz, 2015;Liberali, Reyna, Furlan, Stein, & Pardo, 2011;Toplak, West, & Stanovich, 2011) as well as a (dis)belief in God (Shenhav, Rand, & Greene, 2011). Toplak et al (2011) concluded that the CRT is "a particularly potent measure of the tendency toward miserly processing because it is a performance measure rather than a self-report measure" (p. 1275).…”
Section: Introductionmentioning
confidence: 99%